Fe (III)-Based Ammonia-Free Bath for Electrodeposition of Fe-W Alloys. Issue 9 (11th July 2017) - Nicolenco, A.; Tsyntsaru, N.; Cesiulis, H.
Abstract : Electrodeposited Fe-W alloys are the subject of extensive studies to be applied in versatile engineering applications, and many solutions based on Fe(II) complexes are described for their deposition. However, in aqueous solutions containing dissolved oxygen, Fe(II) compounds are unstable thermodynamically and tend to oxidize to Fe(III) state that decreases the sustainability of the baths. The aim of the present study was to develop an environment-friendly and thermodynamically stable Fe(III)-based electrolyte for electrodeposition of Fe-W alloys with tunable composition. It was found that: (i) concurrent use of two complexing agents as citric and glycolic acids stabilizes Fe(III)-based bath in neutral and weak alkaline medium (no precipitates are formed); (ii) the current efficiency of the process can reach up to 60–70%, which has never been reported before for Fe-W alloys electrodeposition; (iii) nanocrystalline Fe-W coatings containing 11–24 at.% of W can be obtained from Fe(III)-based glycolate-citrate bath at temperature range 20–65°C. The increase in tungsten content in the alloy resulted in decreased grain size up to < 5 nm; (iv) smooth, free of cracks and having deposition rates up to 0.18 μm/cm 1 alloys are successfully electrodeposited at elevated temperatures from elaborated glycolate-citrate electrolyte.